Quality Model for Massive Open Online Course (MOOC) web content - Wan Ab Rahman, Wan Nurhayati; Zulzalil, Hazura; Ishak, Iskandar; Selamat, Ahmad Wiraputra (Insight Society, 2020)
With the philosophy of providing open education to all, Massive Open Online Course (MOOC), which introduced in 2006, has been through its first decade. Despite its popularity and worldwide acceptance, MOOC faces a few criticisms about the weaknesses of its content such as lack of clarity, unstructured, poor design and lack of fundamental initial requirements. This caused by the paucity of understanding among content providers about the facet of qualities contributes to the content. There are some previous efforts to improve the quality of MOOCs, but none focused on the content from the content providers or experts' view. As a result, most of the vital internal quality factors are neglected. Besides, the operational definition for the MOOC content quality factors is still missing or not well-defined. Therefore, this research proposes a quality model for MOOC web content as a content provider’s reference to develop quality MOOC content. In order to achieve that, three basic elements were implemented which is the content’s provider perspective, MOOC content quality dimensions and MOOC content quality factors. Development of MOOC content quality dimension is based on 7C’s model and PDCA for continuity, while the determination of factors involves the process like a revision of the possible factors from literature, factors combination and categorization. This proposed hierarchical model tends to make MOOC's learning more optimistic and beneficial to the learners through the development of high-quality content.